Consuming Health Information and Vulnerable Populations: Factors of Engagement and Ongoing Usage - Staccini, Pascal; Lau, Annie Y.S. (Yearbook of Medical Informatics, 2022)
Objectives: To summarise the state of the art during the year 2021 in consumer health informatics and education, with a special emphasis on “Inclusive Digital Health: Addressing Equity, Literacy, and Bias for Resilient Health Systems”.Methods: We conducted a systematic search of articles published in PubMed using a predefined set of queries. In order to build queries, we have used a common understanding of digital inclusion. Leaving no one behind in the digital age requires not only reaching the most vulnerable populations, but also those people and population groups that are not digitally literate. It implies appropriate access, digital skills, and usability and navigability aspects in the development of technological solutions. Thus, we identified 126 potential articles for review. These articles were screened according to topic relevance and 13 were selected for consideration of best paper candidates, which were then presented to a panel of international experts for full paper review and scoring. The top five papers were discussed in a consensus meeting. Four papers received the highest score from the expert panel, and these papers were selected to be representative papers on consumer informatics for exploring inclusive digital health in the year 2021.Results: Bibliometrics analysis conducted on words found in abstracts of the candidate papers revealed five clusters of articles, where the clustering outcomes explained 93.58% of the dispersion. The first cluster analysed the use of mobile apps to improve quality of communications between racial subgroups (e.g., Black patients and their family members) and healthcare professionals, and reduce racial disparities in core palliative care outcomes. The second cluster revealed studies reporting health literacy and experience of patients with specific diseases or impairments (e.g., type 2 diabetes, asthma and deaf people). The third focused assessing the effectiveness of interactive social media interventions on changing health behaviors, health outcomes and health equity in the adult population. The fourth targeted people with limited health literacy, as well as potentially disadvantaged or marginalized groups (people with cerebrovascular or cancer problems, students with mental problems, African American Young adults), and explored how social media may help reduce health disparities and improve health outcomes. The last explored health literacy levels among groups who experience difficulties with health service engagement and retention (patients with cancer or lay consumers of online disease information).Conclusions: Although the query was built to address consumer inclusiveness and digital health, without specifying any health status or disease, COVID-19 was the topic in a lot of retrieved papers. Beyond the classic health issues targeted by social media (e.g., influencing health behaviors, from smoking and diet adherence to preventative screening and exercise habits), the pandemic has exposed many situations of vulnerability and health inequality. There is universal agreement on the necessity of a healthcare policy that addresses issues of gender, age, sexual orientation, and different cultures to ensure health equity for all, regardless of age or resources available. The place of digital health is studied both as a solution and a possible factor of accentuating healthcare disparities, inequalities, and exclusions. Healthcare providers should implement a digital health literacy plan to make sure health information technology is an option for everyone. Public health policies and health promotion strategies must focus on strengthening and adapting the digital health literacy in known vulnerable subgroups (ethnic and racial minorities, sexual and gender minorities, children and adolescents, elderly people, students population, impaired people, patients with cancer and chronic diseases) increasing citizen technology engagement and guaranteeing equity in access to information and in the skills to manage, discriminate, and apply information to health.
Keywords: Consumer health informatics; health literacy; healthcare disparities; minority groups